Analisis Bibliometrik Pembelajaran Sains Untuk Anak Pra Sekolah - Kamil, Nurhusni; Nurramadani , Lilia; Dewi , Utami Kumala; Wahyuni, Sri (JEA (Jurnal Edukasi AUD), 2023)
This article aims to analyze science learning for early childhood or pre-school children by taking the Scopus database by processing metadata using a bibliometric application over the last 5 years, from 2019 to 2023. The purpose of the bibliometric analysis used in this study was to determine developments during The last 5 years regarding science learning for preschoolers. In particular, this article aims to find out about science learning for preschoolers from 2019 to 2023, main journals, authors, affiliations, countries and documents in the field of early childhood education, trending topics related to the application of science learning for preschoolers, classification and science learning topics. There are 4 ways to collect data in this article, namely: 1) data sources are obtained from Scopus indexed journals; 2) the obtained journal metadata is then downloaded in CSV format; 3) checking the results of the articles and taking them according to research needs; 4) processing the data obtained using a bibliometric application. Data was collected with the keyword "science learning education". The author uses biblioshiny software to analyze and visualize the database that has been obtained. The results of a bibliometric study on the relevance of science, learning and children based on Scopus publications 2019-2023 show that science learning for preschoolers is highly recommended for the purpose of making children understand learning more concretely through experimental and exploratory activities carried out in science activities. The results of this study indicate that the citation analysis shows the number of citations per year from 2019-2023, namely 809 documents